PENGUATAN PROGRAM PENGABDIAN MASYARAKAT MELALUI KEGIATAN KKN BERBASIS MASJID UNTUK MENINGKATKAN KEGIATAN KEAGAMAAN - Stephanie, Erviana; Ibrahim, Maulana; Elzani, Rahma; Suli, Suli; Nataria, Popi (ABDI MAKARTI, 2024)
Real Work Lectures  are intracurricular activities whose implementation takes into account the integration of the Tri Dharma aspects of Higher Education, namely education and teaching, research and community service. The work programs that have been carried out are used to overcome existing problems. and the program has a positive impact on existing problems. Community service activities through mosque-based KKN activities to increase religious activities in Kayu Arang village is a concrete step in strengthening Islam. The UINFAS Bengkulu Real Work Lecture (KKN) carried out is Mosque-Based KKN. Mosque-Based KKN is a KKN activity where student activities are centered on the mosque as the center for the development of religious life for the community. Where Group 66 of the Bengkulu UINFAS KKN was assigned to the Al – Iman Mosque, Kayu Arang Village, Sukaraja District, Seluma Regency. This mosque-based community service activity is carried out to help carry out Islamic activities in Kayu Arang Village. By creating several work programs to help revive Islamic activities in Kayu Arang village. And collaborate with related parties.